2021
DOI: 10.3390/magnetochemistry7110145
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Metal and Metal Oxide Nanoparticles: Principles of Green Chemistry and Raw Materials

Abstract: Increased request for metal and metal oxide nanoparticles nanoparticles has led to their large-scale production using high-energy methods with various toxic solvents. This cause environmental contamination, thus eco-friendly “green” synthesis methods has become necessary. An alternative way to synthesize metal nanoparticles includes using bioresources, such as plants and plant products, bacteria, fungi, yeast, algae, etc. “Green” synthesis has low toxicity, is safe for human health and environment compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 216 publications
0
41
0
Order By: Relevance
“…Chemical synthesis can also restrict the application possibilities and biocompatibility of MNPs [ 166 , 167 ]. Green synthesis, through precursors of biological origin, such as polysaccharides, prevents pollution and mitigates cytotoxicity during the early stages of chemical processes [ 168 ]. Successful synthesis and stabilization of MNPs using these biological macromolecules was achieved in several works by the coordination bonds between the metal salts and functional groups of polysaccharides [ 46 , 72 , 86 , 88 , 105 , 115 , 134 ].…”
Section: Safety Issues Of Mnps and The Role Of Polysaccharidesmentioning
confidence: 99%
“…Chemical synthesis can also restrict the application possibilities and biocompatibility of MNPs [ 166 , 167 ]. Green synthesis, through precursors of biological origin, such as polysaccharides, prevents pollution and mitigates cytotoxicity during the early stages of chemical processes [ 168 ]. Successful synthesis and stabilization of MNPs using these biological macromolecules was achieved in several works by the coordination bonds between the metal salts and functional groups of polysaccharides [ 46 , 72 , 86 , 88 , 105 , 115 , 134 ].…”
Section: Safety Issues Of Mnps and The Role Of Polysaccharidesmentioning
confidence: 99%
“…[10,11] Many benefits of spinel ferrite have also been documented, including its high surface area, magnetic separability, cation distribution, ecofriendly route, low cost, chemical stability, and so on. [12][13][14][15] There have been a few recent reports of spinel ferrites demonstrating various catalytic reactions. For example, Dey et al reported the fabrication of nickel ferrite through a chemical route aided by surfactants for catalytic reduction of nitroaromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Spinel ferrites have drawn a lot of interest in the field of nanotechnology in recent years because of their numerous applications [10,11] . Many benefits of spinel ferrite have also been documented, including its high surface area, magnetic separability, cation distribution, ecofriendly route, low cost, chemical stability, and so on [12–15] . There have been a few recent reports of spinel ferrites demonstrating various catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the chemicals employed in metallic nanoparticle preparation are toxic, and improper treatment of these chemicals could lead to environmental pollution. Therefore, the preparation of environmentally friendly, low-temperature-sintering metallic nanoparticles has become a research trend [ 21 , 22 , 23 , 24 ]. In past research [ 18 , 25 , 26 ], reports clearly demonstrated that ascorbic acid is a popular reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Silver, copper, and gold are the three most frequently studied metals for nanoparticles [ 10 , 11 , 24 , 27 ]. Silver and gold are costly.…”
Section: Introductionmentioning
confidence: 99%